An intrinsic descriptor of perovskite cobaltites for catalytic peroxymonosulfate activation toward water remediation - Wang, K.; Han, C.; Li, F.; Liu, Y.; Shao, Zongping; Liu, Lihong; Wang, Shaobin; Liu, Shaomin (ELSEVIER, 2023)
A series of strontium cobaltite perovskite oxides with various dopants (SrCo0.95M0.05O3-δ, M=Fe, Sc, Co, Zn, Gd) are designed for catalytic peroxymonosulfate (PMS) activation to degrade aqueous organic pollutants and the correlations between their crystalline structure and surface properties to catalytic activity were comprehensively investigated. SrCo0.95M0.05O3-δ displays three crystalline structures depending on the dopant metals and exhibits different catalytic activities. Among the structures and properties, Co-O bond length significantly affects the lattice oxygen diffusivity and Co2+/Co3+ redox capacity, governing the overall PMS activation, and is suggested as a descriptor for PMS activation. This study provides new insight to the reaction pathways and the structure-activity correlation for new design of effective perovskite oxides for PMS-based oxidation process toward wastewater treatment and other catalytic processes.